T003 How TDCS polarises a highly folded cortex - Bikson, M. (Clinical neurophysiology, 2017)
The highly convoluted surface of human cortex influences current flow and resulting neuromodulation produced by transcranial Direct Current Stimulation (tDCS). The canonical findings that “anodal”/“cathodal” stimulation excite/inhibit cortex are first explained from the perspective of a smooth cortical surface using concentric spheres modeling and data from animal studies. MRI-derived models with gyri-specific resolution predict that cortical folding produces an oscillating pattern of polarization both under and between electrodes. Data from modern animals studies provides hypotheses for how a mixed cortical polarization pattern none-the-less can produce stimulation polarity specific effects. Network oscillations provide a substrate to “bind” mixed polarization across regions leading to regional specific effects. Non-linear neuronal processing and synaptic plasticity mechanisms support rectification of mixed polarization by tDCS. Consideration of cortical folding thus enriches understanding of tDCS mechanisms and informs how tDCS protocols should be designed.